FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM VALUE DENGAN MANAGERIAL OWNERSHIP SEBAGAI VARIABEL MODERASI - Gracia Jocelyn Jocelyn; Yanti Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to obtain empirical evidence about the effects of intellectual capital, capital structure, and profitability on firm value using managerial ownership asmoderating variable. The sample in this study was selected using purposive sampling method amounted to 53 manufacturing companies listed on the Indonesia Stock Exchange (IDX) on the 2017-2019 period that fit the criteria. This study uses the E-views 11 program to analyze data. The results of this study indicate that profitability has a significant positive effect on firm value, while intellectual capital and capital structure show insignificant results. Besides, it can be concluded that managerial ownership as a moderating variable also cannot moderate the effect of intellectual capital, capital structure, and profitability on firm value. The implication of this research is that good management of the company's assets and funding is needed in order to achieve good corporate value in the eyes of investors.